Direct detection of wavelike spatial structure at the bottom of the F region and its role on the formation of equatorial plasma bubble - Patra, A. K.; Taori, A.; Chaitanya, P. P.; Sripathi, S. (My University, 2013)
We present hitherto unrevealed wavelike spatial structures, as seen in the 630 nm airglow intensity using a scanning photometer, prior to the occurrence of equatorial plasma bubble (EPB). The dominant wavelengths in the spatial variation of airglow intensity have excellent correspondence with the spatial separations of periodic plume structures in the radar observations, and the amplitudes of the wave perturbations (6–12%) are significantly more than the commonly quoted 5% seed perturbation used in simulation studies. In contrast, no such airglow structure was observed on EPB free evening. Concurrent ionosonde observations made from the magnetic equator, although displayed satellite trace on some occasions, did not show one-to-one correspondence between the occurrence of satellite trace and EPB, a finding that is inconsistent with a recent suggestion that satellite trace can be used as a precursor of EPB occurrence. The new findings are discussed in the light of current understanding of the day-to-day variability in EPB including its prediction.
Keywords: Equatorial plasma bubble; F region; EPB